2002
DOI: 10.1523/jneurosci.22-01-00010.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Tyrosine Phosphorylation of Neuronal Proteins Including Tau and Focal Adhesion Kinase in Response to Amyloid-β Peptide Exposure: Involvement of Src Family Protein Kinases

Abstract: The increased production of amyloid beta-peptide (Abeta) in Alzheimer's disease is acknowledged to be a key pathogenic event. In this study, we examined the response of primary human and rat brain cortical cultures to Abeta administration and found a marked increase in the tyrosine phosphorylation content of numerous neuronal proteins, including tau and putative microtubule-associated protein 2c (MAP2c). We also found that paired helical filaments of aggregated and hyperphosphorylated tau are tyrosine phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
177
1
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(188 citation statements)
references
References 72 publications
7
177
1
3
Order By: Relevance
“…In their studies of COS7 cells co-transfected with tau and fyn, Lee et al demonstrated the association of tau proteins with fyn tyrosine kinase and tyrosine phosphorylation of tau at Y18 [10,12]. Furthermore, Williamson et al showed that treatment of primary rat and human cortical neurons with Aβ peptides promotes a transient activation of various signaling proteins including fyn, and tyrosine phosphorylation of neuronal proteins, such as tau [19]. These reports have suggested that fyn kinase may mediate tau tyrosine phosphorylation at Y18 and Y29 and have a role in neurodegeneration [10,12,19].…”
Section: Discussionmentioning
confidence: 99%
“…In their studies of COS7 cells co-transfected with tau and fyn, Lee et al demonstrated the association of tau proteins with fyn tyrosine kinase and tyrosine phosphorylation of tau at Y18 [10,12]. Furthermore, Williamson et al showed that treatment of primary rat and human cortical neurons with Aβ peptides promotes a transient activation of various signaling proteins including fyn, and tyrosine phosphorylation of neuronal proteins, such as tau [19]. These reports have suggested that fyn kinase may mediate tau tyrosine phosphorylation at Y18 and Y29 and have a role in neurodegeneration [10,12,19].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, partial TrkA mRNA silencing paradoxically favored neuronal survival, suggesting that the NGF receptor may switch from pro-survival to pro-apoptotic action in the absence of its specific ligand. In addition, pharmacological inhibition of Cdk and Src kinases, known to trigger amyloidogenesis by affecting APP phosphorylation and processing, [69][70][71][72] reduced the TrkA and PLCg phosphorylation levels and rescued neuronal cultures from death. Relevantly, in p75-silenced neurons, TrkA did not appear phosphorylated after NGF removal and the interruption of the amyloidogenic pathway was prevented.…”
Section: Ngf-deprived Hippocampal Neurons: the Amyloid Cascade And Tamentioning
confidence: 99%
“…Neuronal cultures were prepared from embryonic day 18 rat embryos as previously described (Williamson et al, 2002). Essentially, embryos were removed and their fetal brain cortices dissected and freed of meninges.…”
Section: Primary Cortical Neuronal Culturesmentioning
confidence: 99%
“…The procedures for Western blotting and densitometry image analysis were previously described (Williamson et al, 2002). Briefly, cells were washed three times in ice-cold TBS (25 mM Tris, pH 8.0, 140 mM NaCl, and 5 mM KCl) and lysed by scraping into hot (1001C) 2 Â sodium dodecyl sulfate (SDS) polyacrylamide gel electrophoresis (PAGE) sample buffer, heated to 1001C for 5 min, and then centrifuged at 15 800g(av) for 5 min.…”
Section: Western Blotting and Densitometry Image Analysismentioning
confidence: 99%